Administrative Planning of Waste Management for Environmental Development in the Phadungphan Phatthana Community in the Nong Chok Area of Bangkok to Create Sustainability - Konkhum, Piraporn; Tonsakun-aree, Chanphen; Toobkaew, Anuchama; Chaiponoi, Somkid; Mahamud, Tosaporn (Chophayom Journal, 2024)
The planning and management of waste to improve the environment in the Phadungphan Phatthana in the Nong Chok area of Bangkok to create sustainability is crucial for achieving sustainability and enhancing the quality of life for residents. The primary issue identified is the increase in waste volume and improper waste management, which negatively impacts the environment, health, and the quality of life in the community. Therefore, this research aims to study effective waste management methods in the community and promote community participation in waste management and environmental development sustainability. This research is action-oriented, using methods to survey and analyze waste management practices in the Phadungphan Phatthana Community, including promoting community involvement. The study findings indicate that reducing waste at the source, efficient waste separation, recycling, and proper waste disposal are key factors for effective waste management. Additionally, raising awareness and educating the community, establishing a community committee for waste management, and encouraging public participation in all stages of waste management help the community engage in sustainable environmental development. The research results highlight that campaigns and education, creating incentives for waste separation and recycling, and promoting community involvement are essential for effective and sustainable waste management. The findings can serve as a model for developing waste management in other communities and improving the quality of life and environmental sustainability. Keywords: Environment, Waste Management, Sustainability